Pengaruh Program Membership dan Experience Marketing Terhadap Retensi Pelanggan Pada Bisnis Ritel (Studi Pada Alfamart di Kota Kendal) - Anggraeni, Dhiah Marta; Rivai, Alimuddin Rizal (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
In the increasingly competitive retail industry retaining existing customers has become a crucial strategy to ensure business sustainability and profitability. This study aims to examine the influence of membership programs and experience marketing on customer retention at Alfamart in Kendal City. A quantitative approach with an associative research design was applied. Data were collected through questionnaires distributed to 122 respondents selected based on specific criteria and analyzed using multiple linear regression. The results show that both membership programs and experience marketing significantly influence customer retention, with experience marketing having a more dominant effect. The coefficient of determination (R²) of 87.6% indicates that the combination of both variables explains most of the variation in customer retention. These findings highlight the importance of delivering engaging shopping experiences and providing relevant membership benefits as part of long-term customer loyalty strategies. This research is expected to contribute to the development of experiential and relational marketing strategies in the modern retail sector.
Keywords: Membership Program; Experience Marketing; Customer Retention; Modern Retail; Alfamart